ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN DAERAH KABUPATEN SIDOARJO TAHUN ANGGARAN 2020-2024 - Ica Wulandari; Nurul Lathifah (LPPM STIE YKPN Yogyakarta, 2025)
This study aims to evaluate the financial performance of the Sidoarjo Regency Government using financial ratio analysis. The research is based on Regional Budget Realization Reports (LRA) from 2020 to 2024 obtained from official website of the Regional Financial and Asset Management Agency (BPKAD) of Sidoarjo. The financial ratios analyzed include independence, effectiveness, efficiency, and local revenue growth. The findings indicate a gradual improvement in financial independence, moving from a “participatory” category to “delegative” in the final year. The effectiveness ratio consistently exceeded 100%, demonstrating the government’s ability to surpass local revenue targets annually. The efficiency ratio fluctuated, with two years considered efficient and three years inefficient. The local revenue growth ratio showed a notably positive trend, especially in the last two years. These results reflect the overall improvement in financial management, though expenditure efficiency still requires improvement. This study recommends strengthening budget efficiency strategies and optimizing local revenue sources to enhance financial performance.